TOP MANAGEMENT TEAM AND COMPANY PERFORMANCE IN BIG COUNTRIES VS SMALL COUNTRIES - Joy Elly Tulung; Olivia S. Nelwan; Victor P.K. Lengkong (Universitas Hayam Wuruk Perbanas, 2012)
So far, there has been little research related to the impact of globalization on corporate governance,particularly the internationalization of the board of directors of international orglobal companies. Besides that, there has been little attention to the nationality compositionof top management. In connection with such a condition, this study attempts to investigatehow the Nationality Diversity in Top Management Team (TMT) affects Company Performancein big countries in Europe versus small countries in Europe. The research data weremanagement boards of companies in 111 companies: 30 in Germany, 38 in France, 25 in theNetherlands, and 18 in Belgium. The whole dataset was provided by Van Veen and Marsman(2008) and derived from this study on nationality diversity. The study provides several results.First, there is a positive relationship between the nationality diversity of TMT membersand company performance. Second, the size of the companies depends on the size of thecountry; companies in the big countries have more employees than those in the small countries.Third, the result of company performance in the big countries and the small countries isnot significant, so the performance of the companies in the big countries is not better thanthat of the companies in the small countries.